Sleep duration and cardiovascular outcomes - Martyna Lichman; Jakub Przeradzki; Aleksandra Borycka; Barbara Jędrzejewska; Maria Kotulska; Paulina Laskus; Zuzanna Lubczyńska; Zofia Potocka; Katarzyna Rząd; Julia Kochanowska (Kazimierz Wielki University, 2023)
Cardiovascular diseases (CVD) are the leading cause of death worldwide, causing approximately 17.9 deaths annually. Their risk factors are mainly related to an inappropriate lifestyle and include, among others, low physical activity, obesity, hypertension or type 2 diabetes. Nowadays, there is an increase in the incidence of CVD as well as sleeping disorders, so many studies have focused on finding the connection between these phenomena. The impact of sleep duration on the occurrence of cardiovascular diseases and their risk factors was analyzed based on a systematic analysis of the literature. The review was carried out using keywords, based on data contained in the Google Scholar search engine database, in the PubMed scientific database and medical electronic journals. The analyzed studies indicate that sleep duration, its both excessive shortening and lengthening, as well as poor quality, may be associated with CVD, their risk factors and increased overall mortality. Researchers point to the connection between sleep duration and development of hypertension, obesity and type 2 diabetes, with short sleep identified as a stronger risk factor. In addition long sleep was associated with poor health and overall worse results of the subjects more often than short sleep. This suggests that long sleep may not be the cause, but a consequence of yet undiagnosed, coexisting chronic diseases. The results indicate the need to assess sleep disorders as a goal for primary and secondary prevention of CVD and reduction of their risk factors. The importance of long sleep remains ambiguous, whether it is the reason for health deterioration or results from it and requires further research. Large intervention studies are also still needed to assess whether improvements in sleep duration and its quality can reduce cardiovascular risk and improve long-term health outcomes.